A Case Study on the Application of a Human Performance Technology Model to a Sports Product Manufacturing Company. Issue 5 (5th June 2020) - Osam, E. Kobena; Nold, Kevin
Abstract: This case study sought to apply the principles of human performance technology (HPT) using Rummler's (2007) Result Improvement Process (RIP) model at XYZ Inc. XYZ Inc. is a sports product manufacturing company located in the Midwestern United States that specializes in the production of cutting‐edge sports technology for athletes and trainers through research and development. Data were collected through interviews and observation of the production process. Emerging themes from analyzing the interview data were combined with observation notes to complete a performance analysis. Results indicated that XYZ Inc.'s issues with product assembly and outdated production manuals were the problems affecting production. Relocating manufacturing operations and updating production manuals were recommended as potential interventions to solve the performance problem.